Translocation of outer membrane vesicles from enterohemorrhagic Escherichia coli O157 across the intestinal epithelial barrier - Krsek, Daniel; Yara, Daniel Alejandro; Hrbáčková, Hana; Daniel, Ondřej; Mančíková, Andrea; Schüller, Stephanie; Bielaszewska, Martina (Frontiers in Microbiology, 2023)
Outer membrane vesicles (OMVs) carrying virulence factors of enterohemorrhagic Escherichia coli (EHEC) are assumed to play a role in the pathogenesis of life-threatening hemolytic uremic syndrome (HUS). However, it is unknown if and how OMVs, which are produced in the intestinal lumen, cross the intestinal epithelial barrier (IEB) to reach the renal glomerular endothelium, the major target in HUS. We investigated the ability of EHEC O157 OMVs to translocate across the IEB using a model of polarized Caco-2 cells grown on Transwell inserts and characterized important aspects of this process. Using unlabeled or fluorescently labeled OMVs, tests of the intestinal barrier integrity, inhibitors of endocytosis, cell viability assay, and microscopic techniques, we demonstrated that EHEC O157 OMVs translocated across the IEB. OMV translocation involved both paracellular and transcellular pathways and was significantly increased under simulated inflammatory conditions. In addition, translocation was not dependent on OMV-associated virulence factors and did not affect viability of intestinal epithelial cells. Importantly, translocation of EHEC O157 OMVs was confirmed in human colonoids thereby supporting physiological relevance of OMVs in the pathogenesis of HUS.